Control of oral cancer in developing countries: A WHO Meeting (1984)
Oral cancer is one of the 10 most common cancers in the world. In Bangladesh, India, Pakistan, and Sri Lanka it is the most common and accounts for about a third of all cancers. More than 100 000 new cases occur every year in south and south-east Asia, with poor prospects of survival. The importance of oral cancer as a public health priority is underscored by the fact that the suffering, disfigurement, and death it causes need not occur. The commonest cause of oral cancer—tobacco use—is well known and can be eliminated. For the oral cancer cases that do occur, detection at an early stage is possible, allowing simple inexpensive treatment, and resulting in long-term survival. Enough is already known about the disease and its prevention for action to be taken. With firm commitment, correct priorities, and concerted efforts by governments and individuals, strategies can be designed, programmes can be implemented, and the disease can be prevented. The economic saving in health care costs to a country, by itself, justifies these steps; the prevention of suffering and death of oral cancer victims makes them mandatory. This article reviews the current knowledge about the epidemiology, etiology, pathology, prevention, and treatment of oral cancer. It describes a strategy for controlling the disease, sets priorities, and recommends actions that governments and individuals can take. Finally, it identifies targets for future research.